Faktor risiko tingginya kadar kolesterol darah total pada penderita penyakit jantung koroner di Banda Aceh - Silvia Wagustina; Eva Fitriyaningsih; Rosi Novita (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Acehnese people have a habit of consuming foods high in saturated fat such as goat curry containing fatty meat, brains, offal. This is due to full work activities, changes in lifestyle and increasing economy. If this diet continues, it can cause cholesterol in the blood to increase and over time will cause blockage in the walls of the heart blood vessels. If the coronary artery blood vessels are blocked, it will cause coronary heart disease.Objective: to determine the risk factors that cause blood cholesterol levels in patients with coronary heart disease.Methods: This research design is descriptive analytical with a cross-sectional approach. The sample is patients with coronary heart disease. The number of samples is 32 people. Sampling was done by purposive sampling. The types of data collected consist of primary data, namely the habit of consuming foods high in saturated fat and secondary data, namely total cholesterol levels. Data analysis in this study used the chi-square test. Data presentation is presented in tabular and textular forms.Result: 29 people have a habit of consuming foods high in saturated fat and high total cholesterol levels. The average consumption of saturated fat is 22,9 grams and cholesterol levels are 246,22 mg / dl. Where the highest fat consumption is 30 grams, the lowest is 8 grams and the highest total cholesterol level is 310 mg/dl, the lowest is 187 mg/dl. There is a relationship with p <0,05.Conclusion: Obesity, physical activity, habit of consuming saturated fat, habit of consuming simple carbohydrates and lack of fiber consumption are risk factors for high blood cholesterol levels in patients with coronary heart disease.